Attitudes of Tourism and Hospitality Students from the National University of Cañete toward Environmental Conservation - Ormeño Vásquez, Phillip (2025)
Tourism and hospitality education in Peru is evolving to incorporate a stronger focus on environmental conservation. In this context, this study aims to assess environmental conservation attitudes of students enrolled in tourism and hospitality programs offered by Peruvian universities. A descriptive, cross-sectional study was carried out among students pursuing a degree in Tourism and Hospitality Management at the National University of Cañete, in Lima, Peru. The research focused on the period from July to December 2018. The final report was completed in 2020. A sample of 45 students was taken from a total population of 281, based on specific selection criteria. The demographic variables considered for this study were: age group, gender, and class shift, alongside the following dimensions: cognitive, affective and reactive. The majority of participants were female (73.3%), within the 20- to 22-year-old group (80.0%), and attended morning classes (64.4%). The highest level of agreement among students was observed for the statement that local hotels should implement appropriate waste management systems (item 2). Furthermore, 86.7% of respondents strongly agreed that plants and animals have the same right to life as human beings (item 20). Similarly, 60.0% of them indicated they would be willing to mobilize others in support of public space conservation (item 26). Overall, the findings suggest that students possess sound cognitive and affective attitudes towards environmental conservation. However, a lower reactive performance requires strategies to foster a deep emotional connection.